Liability Management and Third-Party Fund Mobilisation in Indonesian Islamic Banks: A Systematic Literature Review of Wadiah and mudharabah Instruments - Nuramelia; Nesa Sulistiawati; Sri Selvi Damayanti. S; Ayu Ariska (Institut Agama Islam Persis Bandung, 2024)
Liability management is a critical determinant of Islamic banking performance, since the deposit base mobilised through Sharia-compliant contracts primarily wadiah and mudharabah provides the structural foundation for financing intermediation. Despite the rapid expansion of Indonesia's Islamic banking sector, the conceptual literature on liability management for third-party funds (Dana Pihak Ketiga, DPK) remains scattered across textbooks, regulatory reports, and journal articles, with limited synthesis into a coherent framework. This study addresses this gap by conducting a systematic literature review of liability management practices in Indonesian Islamic banks, with particular focus on the operational characteristics, risk profiles, and managerial trade-offs associated with wadiah and mudharabah-based fund mobilisation. A PRISMA-inspired protocol was applied to identify, screen, and synthesise twenty-eight English- and Indonesian-language sources comprising peer-reviewed journal articles, regulatory reports, and authoritative textbooks published between 2001 and 2024. Sources were thematically coded along four analytic dimensions: contractual structure, product taxonomy, liquidity–profitability trade-offs, and macro-institutional determinants. The synthesis yields three principal findings. First, wadiah and mudharabah operate on substantively different risk-return architectures, with wadiah anchoring short-term liquidity through on-demand non-remunerated deposits and mudharabah supporting medium-to-long-term productive financing through profit-sharing investment accounts. Second, effective liability management requires a structural pairing between fund characteristics and asset deployment, mediated through Asset and Liability Management (ALMA) protocols that guard against maturity mismatch. Third, the success of fund mobilisation is conditioned not only by internal managerial competence but also by external factors public trust, Islamic financial literacy, service quality, and competitive positioning vis-à-vis conventional banks. The study contributes a consolidated conceptual framework for liability management in Indonesian Islamic banks and advances four practical recommendations and three priority directions for future empirical research.